EMOTIONAL BRANDING: PARADIGMA BARU MEMBANGUN BRAND AWARE - Dwi Irawati (SEGMEN Jurnal Manajemen dan Bisnis, 2005)
This article is about  building brand aware. its focus is how brands can influence potencial consumers  make choice ,to buy or not to buy, to consume or not  to consume  certain product. Consumers  never really  understand all the features and attributes that products and services  have unlike  the companies that produce them they do  know that  they prever  some brands to others. This brand preference  tends to steam  from the emotional  needs that people have. the secret to branding  s in adding value, especially  psychological value to products, services, and companies in the form  of intangible benefits-the emotional associations, beliefs, values, and feelings that people  relate to  the brand. this aspect  of the products or services, and not  the attributes and features, that can strongly distinguish in people’s mind or brand from another. emotional branding as a new paradigm connecting products and costumers  really helps  products  and companies  achieving  costumers’brand awareness better than the rational approach nowadays. Keywords: brand, aware, emotional branding